2017
DOI: 10.1093/mnras/stx071
|View full text |Cite
|
Sign up to set email alerts
|

The Auriga Project: the properties and formation mechanisms of disc galaxies across cosmic time

Abstract: We introduce a suite of thirty cosmological magneto-hydrodynamical zoom simulations of the formation of galaxies in isolated Milky Way mass dark haloes. These were carried out with the moving mesh code arepo, together with a comprehensive model for galaxy formation physics, including AGN feedback and magnetic fields, which produces realistic galaxy populations in large cosmological simulations. We demonstrate that our simulations reproduce a wide range of present-day observables, in particular, two component d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
679
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 488 publications
(718 citation statements)
references
References 137 publications
38
679
1
Order By: Relevance
“…For this purpose, we use simulations of stellar halos including only accreted stars (e.g., [4,24,46]). For this particular analysis, we used the cosmologically-motivated particle-tagging models of [4], although we found that we recovered similar results with a particle-tagging model with more diverse accretion histories [26] and the accreted particles from two very different hydrodynamical simulations, Auriga and Illustris [9,10,24,31,47]. In these model accreted halos, most of the stellar halo mass lies at less than 10 kpc galactocentric radius.…”
Section: Mw Peer Stellar Halos Are Diverse Reflecting a Diversity Inmentioning
confidence: 72%
“…For this purpose, we use simulations of stellar halos including only accreted stars (e.g., [4,24,46]). For this particular analysis, we used the cosmologically-motivated particle-tagging models of [4], although we found that we recovered similar results with a particle-tagging model with more diverse accretion histories [26] and the accreted particles from two very different hydrodynamical simulations, Auriga and Illustris [9,10,24,31,47]. In these model accreted halos, most of the stellar halo mass lies at less than 10 kpc galactocentric radius.…”
Section: Mw Peer Stellar Halos Are Diverse Reflecting a Diversity Inmentioning
confidence: 72%
“…Auriga is a suite of high-resolution magneto-hydrodynamical simulations of MW-mass haloes ran with the AREPO code (Springel 2010). The suite consist of 40 haloes, 30 of which have mass, M200 ∈ [1, 2] × 10 12 M , and were first introduced in Grand et al (2017), plus 10 additional lower mass haloes, with M200 masses just below ∼10 12 M (Grand et al 2019a). The Auriga systems are zoom-in resimulations of MW-mass haloes selected from the EAGLE 100 3 Mpc 3 periodic cube simulation (Schaye et al 2015) that are relatively isolated at z = 0, that is have no objects more massive than half their halo mass within a distance of 1.37 Mpc.…”
Section: Aurigamentioning
confidence: 99%
“…The Auriga systems are zoom-in resimulations of MW-mass haloes selected from the EAGLE 100 3 Mpc 3 periodic cube simulation (Schaye et al 2015) that are relatively isolated at z = 0, that is have no objects more massive than half their halo mass within a distance of 1.37 Mpc. See Grand et al 2017 for more details, as well as for illustrations and properties of the central galaxies in the Auriga haloes.…”
Section: Aurigamentioning
confidence: 99%
“…The simulations come in two versions: dark matter only and full baryonic physics included (this entails magetohydrodynamics, gas cooling, star formation, black hole growth, and associated feedback processes). A detailed description of the simulations, the numerical treatment, and the resulting galaxy properties can be found in Grand et al (2017). Here we summarize some of the main features.…”
Section: Numerical Simulationsmentioning
confidence: 99%